COMMUNICATION STRATEGY ON SEXUAL AND REPRODUCTION HEALTH FOR ADOLESCENTS DIFFABLE IN YOGYAKARTA - Pratiwi Rika Mandasari; Yenni Sri Utami; Senja Yustitia (The Indonesian Journal of Communication Studies, 2017)
This research is aims to know health communication strategy and inhibitions in the program of sex- ual and reproductive health (KesPro) performed by Sentra Advokasi Perempuan, Difabel dan Anak (SAPDA) in Yogyakarta. The theme of this research is Health Communication and using planning theory by Charles Berger. Qualitative methodology with descriptive approach is applied for this re- search.The results of research found that communication strategy on sexual and reproductive health for disable teenagers is a development of The P-Process, beginning with an analysis of the problems and research, strategy design and curriculum materials, distribution reproductive sexual health mes- sages through interaction and the use of media proponents, and the last is ongoing relationship with the audience as the monitoring measures. Health communication strategy of SAPDA emphasized on strategy of planning and designing messages, also interpersonal messages in communication with control of emotions, the media advocates, and review the message conveyed to achieve the goals of planing strategy. The barriers that exist are suppositions of taboo, clash towards the values and norms in the community, sign language vocabulary for medical term is limited, the absence curriculum stan- dards, the lack of human resources, and an introvert parent of disable teenagers.